2017
DOI: 10.11646/zootaxa.4244.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cobitis keyvani, a junior synonym of Cobitis faridpaki (Teleostei: Cobitidae)

Abstract: The validity of C. keyvani and C. faridpaki is assessed based on morphological and molecular (COI) data from fishes collected from the type localities of both species. No diagnostic character was found to distinguish both species. Therefore, we treat C. keyvani as a junior synonym of C. faridpaki.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For the genus Cobitis ( S3 Fig ) the values of minimum genetic distance between its species ( S10 Table ) were among the highest for species of the same genus, meaning that these species were clearly separated. High values of interspecific genetic distance for the genus Cobitis have been observed in several studies [ 75 , 76 ]. The only exception are the species Cobitis hellenica Economidis & Nalbant, 1996 and Cobitis arachthosensis Economidis & Nalbant, 1996 for which the maximum genetic distance was 0.0070 and the minimum 0.0000.…”
Section: Resultsmentioning
confidence: 89%
“…For the genus Cobitis ( S3 Fig ) the values of minimum genetic distance between its species ( S10 Table ) were among the highest for species of the same genus, meaning that these species were clearly separated. High values of interspecific genetic distance for the genus Cobitis have been observed in several studies [ 75 , 76 ]. The only exception are the species Cobitis hellenica Economidis & Nalbant, 1996 and Cobitis arachthosensis Economidis & Nalbant, 1996 for which the maximum genetic distance was 0.0070 and the minimum 0.0000.…”
Section: Resultsmentioning
confidence: 89%
“…In Iran, the genus Cobitis includes Cobitis linea , C. avicennae , C. faridpaki (Mousavi‐Sabet et al, 2015) and C. keyvani as a junior synonym of C. faridpaki (Jouladeh‐Roudbar et al, 2017; Jouladeh‐Roudbar et al, 2020; Mousavi‐Sabet, Yerli, Vatandoust, Cevher Özeren, & Moradkhani, 2012). Actually, for a long time, spined loaches from the Southern Caspian basin were considered as C. taenia Linnaeus, 1758 (Abdoli, 2000; Abdoli & Naderi, 2009; Coad, 2021; Kiabi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…T he genus Cobitis is one of the most widely distributed Palearctic freshwater fishes with 18 reported species from Turkey, including C. battalgili, C. bilseli, C. damlae, C. dorademiri, C. elazigensis, C. evreni, C. fahireae, C. kellei, C. levantina, C. phrygica, C. pontica, C. puncticulata, C. simplicispina, C. sipahilerae, C. splendens, C. strumicae, C. turcica and C. vardarensis [1][2][3][4]. A recent study on the spatial heterogeneity of freshwater fishes in the Mediterranean revealed that some populations of this genus are unrecognized species e.g.…”
Section: Introductionmentioning
confidence: 99%